2005
DOI: 10.1021/ja0507259
|View full text |Cite
|
Sign up to set email alerts
|

Influence ofN-Methylation on a Cation−π Interaction Produces a Remarkably Stable β-Hairpin Peptide

Abstract: The methylation of lysine in histone tails is a common posttranslational modification that functions in histone-regulated chromatin condensation, with binding of methylated lysine occurring in aromatic pockets on chromodomain proteins. We have synthesized a highly stable 12-residue beta-hairpin peptide that exploits the histone-related cation-pi interaction between a methylated lysine residue and a tryptophan residue. Thermodynamic analysis reveals significant entropic stabilization of the peptide due to methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 16 publications
7
89
0
3
Order By: Relevance
“…2) (17,20), ¶ we found that methylation of Lys enhanced its interaction with Trp significantly, but that the driving force became more entropically favorable, suggesting an increased hydrophobic component; in contrast, the enthalpic component, attributed to the charge-quadrupole interaction, decreased relative to unmodified Lys (17). This finding led to the question of whether the positive charge in KMe3 indeed is necessary for interaction with an aromatic residue or an aromatic pocket in aqueous solution or whether hydrophobic and van der Waals interactions alone will suffice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) (17,20), ¶ we found that methylation of Lys enhanced its interaction with Trp significantly, but that the driving force became more entropically favorable, suggesting an increased hydrophobic component; in contrast, the enthalpic component, attributed to the charge-quadrupole interaction, decreased relative to unmodified Lys (17). This finding led to the question of whether the positive charge in KMe3 indeed is necessary for interaction with an aromatic residue or an aromatic pocket in aqueous solution or whether hydrophobic and van der Waals interactions alone will suffice.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we have synthesized the neutral analog of KMe3, tert-butyl norleucine (2-amino-7,7-dimethyloctanoic acid; tBuNle), investigated its interaction with Trp in a ␤-hairpin model system, and then compared these results to in vitro binding assays with the HP1 chromodomain. This hairpin model system has been used previously to investigate the cation-interaction between KMe3 and Trp (17). In this model system, we find striking contrasts between the behavior of the two side chains with Trp that provide insight into the role of hydrophobicity and the importance of the charge-quadrupole component of the Trp-KMe3 interaction.…”
mentioning
confidence: 89%
“…If a small aromatic amino acid is in the N-terminal position adjacent to alanine (9,12,18), then there is a measurable but CSI insignificant upfield shift (*0.05 ppm) of the alanine -proton due to the anisotropic effects resulting from the proximity of the aromatic amino acid. However, if the small aromatic amino acid is instead in the C-terminal position (10,13,19) then the upfield shift is chemically significant for CSI (*0.10 ppm). It is interesting to note that the upfield shifts are not additive, and when two small amino acids are incorporated into a model peptide (8,11,17,20,21) the upfield shift is still chemically significant for CSI, but the magnitude does not appreciably increase beyond that of a single small aromatic amino acid in the C-terminal position.…”
Section: Neighboring Amino Acidsmentioning
confidence: 99%
“…[6][7][8] CSI is of particular importance for those designing peptides that form discrete and stable -hairpins, because with relatively straightforward 1D and 2D NMR studies, information about protein secondary structure can be quickly obtained. [9][10][11][12][13][14][15] While CSI also applies to amide proton (HN), - 13 C, carbonyl 13 C, and amide 15 NH chemical shifts, the current study focuses on -proton chemical shifts. 8,16,17 In CSI the -proton of a particular amino acid in the protein is referenced to the random coil value for that amino acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation